2018
DOI: 10.1096/fj.201800673rr
|View full text |Cite
|
Sign up to set email alerts
|

Signature‐oriented investigation of the efficacy of multicomponent drugs against heart failure

Abstract: Increasing attention has been paid to the application of precision medicine in heart failure (HF), and biomarker-based personalized medical care has shown great progress in HF management. Additionally, multicomponent drugs represented by traditional Chinese medicine (TCM) are demonstrating safety and efficacy in the management of HF. However, the potential mechanism is unclear, and the ambiguous clinical locations of TCM remain a hindrance to its extensive application. To meet this requirement, a precise inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…TCM has the advantages of high treatment efficacy and low treatment cost and side effect in the treatment of several diseases, including UC in China for several thousands of years [32][33][34]. After preliminary screening based on ADME properties, 41 potential bioactive compounds of Quyushengxin were screened out.…”
Section: Discussionmentioning
confidence: 99%
“…TCM has the advantages of high treatment efficacy and low treatment cost and side effect in the treatment of several diseases, including UC in China for several thousands of years [32][33][34]. After preliminary screening based on ADME properties, 41 potential bioactive compounds of Quyushengxin were screened out.…”
Section: Discussionmentioning
confidence: 99%
“…Yixinshu Capsule (YXS), a ShengMai-San-derived TCM formula, is widely used in Asia for the treatment of cardiovascular diseases as a conventional drug, [13,14] which has a potent effect on maintaining cardiac function by reducing oxidative stress injury and mitochondrial-mediated apoptosis. [12,13] And a new research [15] had demonstrated that Yixinshu capsule has distinctive treatment features against heart failure, which maybe particularly suitable for heart failure patients with exaltation of FABP3 and CKAP5. However, the quality of existing randomized controlled trials (RCTs) is uneven, and there are no interrelated meta-analysis and trial sequential analysis have been reported, so no definite conclusion has been drawn on this.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] A new research, based on efficacy evaluation in vitro ad in vivo, demonstrates that Yixinshu capsule has distinctive treatment features against heart failure, which maybe particularly suitable for heart failure patients with exaltation of FABP3 and CKAP5. [15] However, no interrelated meta-analysis and trial sequential analysis have been reported and no definite conclusion has been drawn on this.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, metabolomics offers a suitable way to understand disease pathogenesis and the mechanisms of YXSC from the standpoint of a metabolic evaluation. Furthermore, some specific molecular targets (e.g., fatty acid–binding protein 3 and cytoskeleton-associated protein 5), regulated by YXSC against HF, were identified by proteomic analysis in a study reported by us previously (Wei et al, 2019). However, the metabolic phenotype of HF as well as the metabolic regulation of YXSC against HF remains incomplete and therefore unclear.…”
Section: Introductionmentioning
confidence: 99%